2018
DOI: 10.3892/ol.2018.9556
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cytotoxic effect of Ly2109761 on HeLa cells using the xCELLigence RTCA system

Abstract: In the present study, the in vitro cytotoxic effect of a novel transforming growth factor-β receptor inhibitor, LY2109761, was investigated in the human cervix carcinoma HeLa cell lines. For the purpose of the present study, cell index values obtained using the xCELLigence Real-Time Cell Analysis DP instrument, and mitotic, labelling and apoptotic index analysis were used. The results of the present study indicated that LY2109761 affected the cytoskeleton of HeLa cells, decreased the mitotic and labelling inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In the present study, we confirmed by RTCA and MTT that different concentrations of isoimperatorin had significant inhibitory effects on nasopharyngeal carcinoma CNE2 cell proliferation and that the inhibitory effect increased as the concentration increased. Prior studies as well as the RTCA Evidence-Based Complementary and Alternative Medicine results presented here suggest that isoimperatorin may cause DNA damage resulting in loss of the cell's ability to undergo replication and transcription [22,23]. Flow cytometry analysis showed that, compared with the solvent group, isoimperatorin induced the CNE2 cell apoptosis.…”
Section: Discussionmentioning
confidence: 53%
“…In the present study, we confirmed by RTCA and MTT that different concentrations of isoimperatorin had significant inhibitory effects on nasopharyngeal carcinoma CNE2 cell proliferation and that the inhibitory effect increased as the concentration increased. Prior studies as well as the RTCA Evidence-Based Complementary and Alternative Medicine results presented here suggest that isoimperatorin may cause DNA damage resulting in loss of the cell's ability to undergo replication and transcription [22,23]. Flow cytometry analysis showed that, compared with the solvent group, isoimperatorin induced the CNE2 cell apoptosis.…”
Section: Discussionmentioning
confidence: 53%
“…RTCA can monitor infected HeLa cells inoculated onto a gold matrix by measuring the cell index (CI), an indicator that reflects cellular changes, including cell adhesion and cell number ( Roshan Moniri et al., 2015 ; Cetin and Topcul, 2019 ). The CI readouts of the WT strain infected HeLa cells were significantly lower than those of the mutant strains infected cells infected with the mutant strains from 2h to 9h post infection (12h to 21h in the RTCA assay) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cell viability test reveals PSC, PCZ, In order to further compare the cell protective effect of PSCZ, we additionally used an xCELLigence (RTCA) instrument to monitor the survival and growth of these cells in a quantitative, real-time, dynamic manner. This assay approach is superior to traditional endpoint-based viability assays that assess membrane permeability (Yah and Simate, 2020), enabling the assessment of cell survival in a label-free and automated manner throughout a given experimental period (Ceti_n and Topcul, 2019). RTCA approach was used to measure the survival and growth of cells over a 24 h period following injury with H 2 O 2 and these different nanoenzymes preparations.…”
Section: Assessment Of the Ability Of Pscz To Scavenge Reactive Oxygen Species In Vitromentioning
confidence: 99%